1986
DOI: 10.2134/agronj1986.00021962007800050012x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dicyandiamide‐Amended Fertilizers on Kentucky Bluegrass1

Abstract: Dicyandiamide (DCD), a nitrification inhibitor, is a 67% N compound of low volatility that can be incorporated into fertilizer granules. Urea, ammonium sulfate (AS), and a complete fertilizer (COMP), all amended with DCD so that I 0% of the N was derived from DCD, were evaluated in field studies at West Lafayette, IN, on 'Wabash' Kentucky bluegrass (Poa pratensis L.) grown on Toronto silt loam (fine-silty, mixed, mesic Udollic Ochraqualfs). Urea, AS, sulfur-coated urea (SCU), and isobutylidene diurea (IBDU) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The amount ofDCD in this product was insufficient to inhibit nitrification. Mosdell et al ( 1986) reported similar turfgrass responses to urea and ammonium sulfate products with 10% DCD.…”
Section: Clipping Yields and Colormentioning
confidence: 78%
“…The amount ofDCD in this product was insufficient to inhibit nitrification. Mosdell et al ( 1986) reported similar turfgrass responses to urea and ammonium sulfate products with 10% DCD.…”
Section: Clipping Yields and Colormentioning
confidence: 78%
“…Apparently, the slow release N sources did not release N sufficiently to meet the crop's requirements, and rainfall was light, limiting NO3-leaching losses (Elkashif et al, 1983). Mosdell et al (1986) observed that with fall applied N, there was more NH4+-N in the soil of DCD treated plots than IBDU treated plots the next spring. Forage grass yield response to residual N was greater, however, in IBDU and SCU plots than the DCD treated plots (Mosdell et al, 1986).…”
Section: Introductionmentioning
confidence: 94%